Editorial: Further work on educational leadership and social justice - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

The adaptive challenge of social justice in educational leadership - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Urban school district financing policy brief - Snowden, Sir (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl

Overview of the policy cycle in educational leadership - Haynes, Norris M (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl

Educational leadership policy briefs: Perspectives of doctoral students - Haynes, Norris M; Yavuz, Olcay (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl

Editorial (Fall 2020) - Yavuz, Olcay (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl

Targeted professional development strategies to increase teachers’ efficacy for educating students with special needs - Yavuz, Olcay (Çağdaş Yönetim Bilimleri Dergisi, 2020)
There is a significant increase in the number of students with disabilities. However, many general education teachers report that they feel ill-equipped to educate a classroom of students with diverse special education and learning needs. In this qualitative study, the structured focus group interviews were conducted to determine the PD opportunities and characteristics that general education teachers perceive to influence their sense of self-efficacy for educating students with special needs. The results of the focus group discussions revealed that there are several targeted professional development strategies to increase teachers’ efficacy for educating students with special needs. This study makes recommendations for the research supported professional development activities, focused on educating students with special needs, provided to general education teachers.
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Quantitative explorations of teacher self-efficacy towards students with special needs: Research Article - Arterbery, Denise Hart; Yavuz, Olcay (FIRE: Futuristic Implementations of Research in Education, 2020)
Teacher self-efficacy has been linked to positive student outcomes. This quantitative research study aimed to examine the mindsets and behaviors of regular education teachers concerning their ability to educate students with special needs. The modified Teacher Self Efficacy Survey was administered to general education teachers. Data revealed that general education teachers feel less efficacious for educating students with special needs in the areas of engagement, instructional strategies, and classroom management. This study makes recommendations for professional development, focused on educating students with special needs, provided to general education teachers. Particularly, the findings speak to the need for a more diverse, flexible, and comprehensive approach to implement teacher professional development activities to improve the achievement of students with special needs.
Keywords: Classroom Management; dept.eco; peer-reviewed

Leadership Beyond the Schoolhouse: Preparing Principals to Engage in Advocacy (in Ethridge et al.'s "Advocacy in Education: Research-Based Strategies for Teachers, Administrators, and Teacher Educators") - Trombly, Christopher (2020)
Advocacy has become a crucial professional obligation for school principals. Seen by policymakers as honest brokers who have at heart the best interests of the children and families whom they serve, school principals should offer themselves to policymakers and their staffs as accessible and reliable sources of information about the actual or likely impacts of measures that have already been enacted or that are being introduced. They should be ready to collect, examine, and articulate data of interest to policymakers. Moreover, they should provide compelling stories for those policymakers to remember and retell as they debate, not only education-specific measures, but any policies impacting children’s ability to be healthy, safe, engaged, supported, and challenged.
Keywords: dept.edl

Preparing principals for leadership beyond the schoolhouse - Trombly, Christopher E.; Griffith, D (Advocacy in Education: Research-Based Strategies for Teachers, Administrators, Parents, and the Community, 2020)
Keywords: dept.edl

Learning in the time of COVID-19: capitalizing on the opportunity presented by the pandemic - Trombly, Christopher E. (Journal of Professional Capital and Community, 2020)
Purpose: This paper addresses the current disruption in the educational status quo ante that has been caused by the worldwide outbreak of COVID-19. Its purpose is to suggest how practicing educators, their professional associations and the university-based researchers with whom they partner might capitalize on the unanticipated opportunity to impact education policy that the pandemic presents. Design/methodology/approach: The author draws upon his own preparation and experiences – first as a long-time practitioner in the elementary and secondary school setting, then as a university professor – to offer insights and suggestions to practicing educators, their professional associations and the university-based researchers with whom they partner. Findings: Despite the unexpected challenges that the COVID-19 pandemic has presented to educators – challenges to which educators around the globe have risen admirably – the current crisis also affords practicing educators, their professional associations and the university-based researchers with whom they partner to change the status quo ante for the better. Originality/value: The particular value of this piece is twofold: its analysis of the impact of this unanticipated crisis upon education by an author who has served both in the elementary/secondary setting and at the university level, and its assertion that educators must avail themselves of this once-in-a-lifetime opportunity to change the educational status quo ante for the better. © 2020, Emerald Publishing Limited.
Keywords: Collaboration; Community; Professional judgment; dept.edl; peer-reviewed

Educational leadership, leader-member exchange and teacher self-efficacy - Flores, Gabriela L.; Fowler, Denver J; Posthuma, Richard A. (Journal of Global Education and Research, 2020)
Keywords: dept.edl; peer-reviewed

Examining student achievement, teacher effectiveness, and merit pay in a rural school district - Boudreaux, Mary; Faulkner, Jill (Voices of Reform, 2020)
Keywords: dept.edl; peer-reviewed

COVID-19 elevating the problem of plagiarism: The implied social contract of academic integrity - Gregory, Jess L. (Delta Kappa Gamma Bulletin, 2020)
Keywords: COVID-19; COVID-19 pandemic; EDITORIAL boards; ICELAND; dept.edl; ⛔ No DOI found

Using shared digital documents to increase collaboration and engagement - Gregory, Jess L. (Delta Kappa Gamma Bulletin: Collegial Exchange, 2020)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

The role of ego threat in professional growth: Fulfilling the ethical intentions of the SEED Model - Gregory, Jess L.; Mebane, Karreem A. (Educational Practice and Theory, 2020)
Schools and education in general have made an implicit and, we would assert, explicit promise to society to educate all the children in their care. Unfortunately, there are achievement gaps that illustrate how schools have broken this promise. Teacher evaluation and other accountability measures have been heralded as the answer to this problem. Educator ego threat impedes the implementation of goal-driven teacher evaluation models and, thus, ethical questions arise. To realize the noble goals of educator evaluation, leaders must attend to ethical concerns and to the human aspects of ego threat.
Keywords: Educational leadership; Ego threat; Goal-setting models; Teacher evaluation; Teacher performance; dept.edl; dept.rec; peer-reviewed